Carbidopa/levodopa dose elevation and safety concerns in Parkinson's patients: a cross-sectional and cohort design. Issue 6 (11th December 2012) - Brodell, David W; Stanford, Nicole T; Jacobson, Charles E; Schmidt, Peter; Okun, Michael S
Abstract : Objective: Sinemet, a combination drug containing carbidopa and levodopa is considered the gold standard therapy for the treatment of Parkinson's disease (PD). When approved by the Food and Drug Administration (FDA) in 1988, a maximum daily dosage limit of 800 mg (eight tablets) of the 25/100 carbidopa/levodopa formulation was introduced. Overall, the FDA approval was a historic success; however, the pill limit has been hardcoded into many online medical record systems. This study investigates the 800 mg threshold by using a prospectively collected database of patient information. Design: A retrospective cohort study: (Part I) cross-sectional, (Part II) longitudinal. Setting and participants: PD patients at a Movement Disorders Center in a large academic, tertiary medical setting. Outcome measures: An analysis was performed using carbidopa/levodopa at dosages below and above the 800 mg threshold. A secondary analysis was then performed using two consecutive clinic visits to determine the effects of crossing the 800 mg threshold. Comparisons were made on standardised scales. Results: There was no significant difference in motor, mood and quality-of-life scores in patients consuming below and above the 800 mg carbidopa/levodopa threshold, though a mild worsening in dyskinesia duration was noted without worsening in dyskinesia pain and disability. In PD patients who crossed the 800 mg threshold between two consecutive clinic visits, a significant improvement in depressive symptoms and quality-of-life measures was demonstrated, and in these patients there was no worsening of motor fluctuations or dyskinesia. Conclusions: The data suggest that PD patients have the potential for enhanced clinical benefits when eclipsing the 800 mg carbidopa/levodopa threshold. Many patients will likely need to eclipse the 800 mg threshold and pharmacies and insurance companies should be aware of the requirements that may extend beyond approval limits.